Development of structured zeolitic catalysts for the process of hydroisomerization of n-hexane - Pastvová, Jana (Univerzita Pardubice, 2019)
The hydroisomerization of linear or low branched alkanes through alkenes is a significant process for the refining of C5 to C6 hydrocarbon fractions to increase the octane number of automotive fuels. The hydroisomerization leads to the conversion of linear alkanes with a low octane number to branched isomers with a sufficiently high octane number. The bifunctional heterogeneous catalysts are a combination of an acid catalyst consisting of oxides containing acidic active centers and a metal cluster, where the hydrogenation and dehydrogenation of hydrocarbon reactants take place. The zeolite-based catalysts are significant in petroleum industry for the hydroisomerization of alkanes, especially the MOR zeolite type. However, availability of active sites for the n-hexane molecule in MOR zeolite is restricted by slow diffusion in narrow channels, and overall efficiency of the catalytic process is thus limited by transport of molecules. Branched alkanes diffuse even more slowly than linear n-alkanes due to of the higher kinetic diameter. The access of acidic active sites in current industrial catalysts is typically increased by partial dealumination of zeolites, where the aluminum atoms are extracted from the framework of zeolite resulting in positive textural changes in the channel structure of the zeolite but at the same time lowering the concentration of active acidic Br?nsted centers. For these reasons, various post-synthesis methods of zeolites such as desilication, dealumination and fluoridation have been used in this work. The texture parameters of zeolites are adjusted by combination of these methods and allow easier transport of the hydrocarbon molecules to the active sites, therefore achieving a substantial increase in the rate of hydroisomerization reaction and shifting the reaction conditions to lower temperatures where the thermodynamic equilibrium is inclined to forming of multi-branched alkanes. Another important parameter for the hydroisomerization of C6 is the amount of acidic centers contained in the zeolites. The analysis of the role of increased density of strongly acidic protons showed that the high density of non-interacting but close and strongly acidic structural hydroxyl groups significantly lower the activation barrier in the isomerization reaction compared to far-distantacid sites and can provide higher reaction rates compared to state-of-the-art Pt/H-zeolite catalysts.
Vývoj strukturovaných zeolitických katalyzátorů pro procesy hydroisomerizace n-hexanu
Keywords: hydroizomerizace; n-hexan; dealuminace; desilikace; fluoridace; tvarová selektivita; mordenit (MOR); beta zeolit (*BEA); hierarchické zeolity; hydroisomerization; n-hexane; dealumination; desilication; fluorination; shape selectivity; mordenite (MOR); beta zeolite (*BEA); hierarchical zeolite.